2004
DOI: 10.1038/sj.onc.1207066
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation factors VIIa and Xa inhibit apoptosis and anoikis

Abstract: The molecular mechanisms enabling cancer cells to survive loss-of-adhesion-induced apoptosis in the early phases of metastasis remain largely obscure. Interestingly, the overexpression of tissue factor (TF) on tumor cells is associated with successful metastasis and it has now become clear that coagulation factor VIIa (FVIIa), the natural binding partner of TF induces signal transduction in TF-expressing cells. Hence, we investigated the effects of FVIIa-TF interaction on cell survival. We observed that FVIIa,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
77
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 25 publications
1
77
0
Order By: Relevance
“…Therefore one might question the relevance of FVIIa-induced cell survival for tumor growth and metastasis. However, recently we showed that FVIIa, either alone or in combination with FX, also induces survival in cells that have been detached from the extracellular matrix [7]. As loss of adhesion represents one of the key processes in metastasis, this observation supports the hypothesis that coagulation factor-induced cell survival might be of physiological relevance.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Therefore one might question the relevance of FVIIa-induced cell survival for tumor growth and metastasis. However, recently we showed that FVIIa, either alone or in combination with FX, also induces survival in cells that have been detached from the extracellular matrix [7]. As loss of adhesion represents one of the key processes in metastasis, this observation supports the hypothesis that coagulation factor-induced cell survival might be of physiological relevance.…”
supporting
confidence: 69%
“…We assume that DDAVP may counteract platelet defects by increasing VWF/ GPIb-IX complexes, and subsequently reversing VASP phosphorylation. Indeed, it has been demonstrated that GPIb-IX is involved in upregulation of the adhesive function of integrin a IIb b 3 [7]. VASP phosphorylation assessment may provide further information about platelet disorders.…”
mentioning
confidence: 99%
“…For example, during inflammation, microvascular leakage allows PAR2-activating coagulation cascade proteases to gain access to the basolateral aspect of the epithelium (38,39). Indeed, the inhibition of apoptosis by factor VIIa and its co-factor, tissue factor, which can activate PAR2, has been described previously (40,41). However, while levels of active caspase-3 and DNA fragmentation were all lowered by tissue factor in serum-starved BHK-21 cells expressing factor VIIa (40,42), these studies did not examine the direct involvement of PAR2 in the anti-apoptotic mechanism, although it is known that BHK-21 cells express PAR2 and the factor VIIa⅐tissue factor complex activates PAR2 to stimulate intracellular Ca 2ϩ release (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…TF triggers a procoagulant state in advanced cancer when tumor cells come in contact with the blood or when TF-positive microvesicles are increasingly shed into the circulation (2). The evidence is increasing that the TF/fVIIa complex also initiates key pathogenetic mechanisms in cancer, including angiogenesis (3)(4)(5)(6), cell migration and invasion (3,7), and cell survival (8,9). Although activation of coagulation is critical for TF-dependent hematogenous cancer metastasis (10), it is likely that TF activities in cancer progression also involve direct cell signaling triggered by TF/fVIIa complex formation on cancer cells.…”
Section: Introductionmentioning
confidence: 99%